Preparation and characterization of rare earth doped silica laser glass by sol-gel process - Wang, Sa Sa. (2009)
Silica glasses containing neodymium or erbium are important laser glasses because their specific optical transitions centered at 1.06 \im and 1.54 (am, respectively, have important applications in optical telecommunications and sensors. The sol-gel method is highly advantageous in that it provides a uniform distribution of relatively high concentration of Nd and Er ions in silica hosts with respect to conventional processing techniques, and it provides the flexibility in controlling the material in such shapes as powder, thin film and bulk material.